INTEGRASI WAHYU DAN AKAL UNTUK MEMBANGUN ARGUMENT YANG KOKOH BIDANG ILMU KALAM - Ahmad Uli Nuha (Aqidah-Ta: Jurnal Ilmu Aqidah, 2025)
This article discusses the importance of integrating revelation and reason in building a solid theological argument in the science of Kalam. Revelation as a source of absolute truth and reason as a rational instrument of human beings cannot be separated in the process of formulating and defending Islamic creed. Through a historical approach and analysis of the thoughts of classical and contemporary figures, this article shows how both complement each other in answering the challenges of science and da’wah. The results of this study confirm that the integration of revelation and reason is a crucial epistemological approach in the development of rational, contextual, and transformative Islamic thought, especially in education and da’wah.